DAYA HAMBAT EKSTRAK BIJI MENGKUDU TERHADAP PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTANS - Wawan Ariyanto; Sadimin Sadimin; Sariyem Sariyem (Jurnal Kesehatan Gigi, 2016)
TITLEInhibitory effect of mengkudu seeds extract against the growth of Streptococcus mutansABSTRACTOne of the problems in the oral cavity are dental caries. Dental caries is caused by bacteria Streptococcus mutans. Mengkudu seed is one of the herbs that have antibacterial effects that is composedof linoleic acid and essential fatty acids, alkaloids, saponins, tannins and cardiac glycosides. The purpose of this study was to determine the inhibitory Mengkudu seed extract on the growth of Streptococcus mutans.This research uses descriptive method. The study design is experimental. This study uses a concentration of 100% and 8 repetitions. Using a control group Sodium Physiological 0.9%. Research subjects in this study is the bacteria Streptococcus Mutans. In this study, bacteria were grown on PCA media by paper disc which had previously been dipped in water 100% noni seed extract, then take a paper disk back Sodium Physiological dipped 0.9% as a control group and in place on the media PCA, then incubated for 1 x 24 hours. Once it is done in the area oligodinamik measurements with calipers (mm). Analysis of the data used is descriptive kuantiatif.The results showed that noni seed extract can inhibit the growth of bacteria Streptococcus mutans. While having inhibitory still relatively very weak which is an average of 8 times the experiment is 8.32mm and it is hoped this research can be developed again with another method, in order to get results in maximum. Keywords : Dental caries, Streptococcus mutans, noni seed extract